Tintoretto by Melania Mazzucco: a poetic of ekphrasis (Anclajes, 2020)
Melania Mazzucco (1966), who is a Roman writer, dedicates numerous ecfrastic passages to the work of Tintoretto, a famous late Renaissance painter whom she considers a milestone in her own artistic and vital trajectory. In the biographical novel La lunga attesa dell’angelo (2008), Mazzucco recreates the artist's thoughts during his feverish agony, with special emphasis on the ambiguous relationship he had with his daughter and disciple Marietta; while in Il Museo del Mondo, a collection of essays on works of art, the writer characterizes Tintoretto as a father. Through the ekphrasis, both critic and literary (Riffaterre), of the work of the Venetian painter, Mazzucco outlines central guidelines of her poetics, such as the recovery of history, the different ways of vital and artistic filiation, the anachronism of the images and the attitude of complicity regarding of the spectator, among others.
Keywords: Melania Mazzucco; Tintoretto; plastic arts; ekphrasis; poetics